Prevalences of respiratory viruses and bacteria in Western Canadian commercial feedlot calves detected using a single metagenomic sequencing protocol vary during the first two weeks of arrival and by age group - Donbraye, Emmanuel; McLeod, Lianne; Carson, Claire N.; Chai, Zhijian; Lacoste, Stacey R.; Herman, Emily K.; McCarthy, E. Luke; Hill, Janet E.; Erickson, Nathan E. N.; Pollock, Colleen; Links, Matthew G.; Otto, Simon J. G.; et al. (Frontiers in Veterinary Science, 2026)
IntroductionDetection of pathogens associated with bovine respiratory disease (BRD) typically involves several laboratory tools, with results limited to a defined list of targets. This study adapted a previously reported method for metagenomic sequencing of nasal swabs to describe sequencing data from BRD associated viruses. Changes in virus composition were identified between arrival to a feedlot and 14 days on feed (DOF). These data were also assessed for the simultaneous characterization of bacteria and antimicrobial resistance genes (ARGs).MethodsNasal swabs were obtained from fall-placed calves (FPC) and yearlings (YRL) from western Canadian commercial feedlots. Evidence of respiratory viruses were identified by sampling 380 animals during processing on arrival to the feedlot and again after 14 DOF using Nanopore metagenomic sequencing.ResultsTwenty-one distinct viruses from 12 viral families were identified, with multiple viruses detected in most samples. In FPC arrival samples, the most common BRD associated viruses were bovine rhinitis B virus (BRBV; 46%), bovine coronavirus (BCoV; 32%), influenza D virus (IDV; 17%), bovine respiratory syncytial virus (BRSV; 8.5%), and bovine parainfluenza virus 3 (BPIV-3; 4.2%). The prevalences of bovine herpesvirus type 1 (BoHV-1; 2.7%), BPIV-3 (12%), BRSV (26%), and IDV (51%) were higher in 14 DOF samples compared to arrival samples (p < 0.05). Bovine viral diarrhea virus 1 (BVDV-1) and 2 (BVDV-2) were rarely detected at either time. The most prevalent viruses detected in YRL arrival samples were BRBV (42%), BRSV (39%), BPIV-3 (20%), IDV (16%), BCoV (12%), and BVDV-2 (7.5%). The prevalences of BRSV (60%), BPIV-3 (39%), and BVDV-2 (17%) were higher in 14 DOF samples than arrival samples (p < 0.05). BRSV (OR 7.0, 1.7–29) and BPIV-3 (OR 5.7, 1.5–21) were more likely to be detected in arrival samples from YRL than FPC (p = 0.01). In 14 DOF samples, BPIV-3 (OR 4.9, 1.3–19, p = 0.02) and BVDV-2 (OR 13, 2.0–83, p = 0.01) were identified more frequently in YRL than FPC. These data allowed the identification of respiratory bacteria and 33 ARGs in parallel with assessment of the viral components. The most prevalent bacteria detected in FPC at arrival were Mannheimia haemolytica (35%), Histophilus somni (35%) and Pasteurella multocida (23%). Detection of M. haemolytica increased at 14 DOF (p = 0.02), while P. multocida detection decreased (p = 0.03). At both arrival and 14 DOF in YRL, M. haemolytica was the most prevalent bacterium, followed by P. multocida and H. somni with no significant differences between arrival and 14 DOF samples. ARGs were detected more frequently in the 14 DOF samples than at arrival for both FPC (p = 0.03) and YRL (p = 0.01). The most commonly detected ARGs were associated with resistance to lincosamides and aminoglycosides; however, ARGs associated with other antimicrobials used in cattle including tetracyclines were also identified.DiscussionChanges in the prevalence of BRD associated viruses early in the feeding period reflect transmission and the potential risk of developing the disease. Frequent detection of BCoV, BRSV, and BPIV-3 in newly arrived feedlot cattle suggests the need for improved vaccination before shipping or limitations in existing commercial vaccine preparations.